Dermoscopy Features of Acquired Perforating Dermatosis Among 39 Patients - Wang, Wenju; Liao, Yansen; Fu, Lixin; Kan, Bei; Peng, Xiaodong; Lu, Yonghong (Frontiers in Medicine, 2021)
In this report, we concluded there are four dermoscopic features of RPC including a yellow-brown homogeneous structureless area in the center of the lesion, dotted and linear vessels distribution radially and a dam shape uplift at the periphery, as well as a white irregular ring surrounding the lesion. There are 3 features, including the yellow-brown homogeneous structureless area in the center of the lesion, the dotted and linear vessels distribution radially and the white irregular ring surrounding the lesion were correspond to the report of Emma Ormerod et al. These features are also similar to those previously discribed in 3 separated reports of 7 cases with RPC. In our report, we found a new dermoscopic features: the dam shape uplift at the periphery. These finding may be contributed to improve the rate of clinical diagnosis of RPC. The data in the manuscript is original and the manuscript is not under consideration elsewhere. All authors have read and approved all versions of the manuscript, its content, and its submission to the journal. None of the authors has any potential financial conflict of interest related to this manuscript We have read and have abided by the statement of ethical standards for manuscripts submitted to your journal. The authors certify that they have obtained all appropriate patient consent forms. In the form, the patients have given their consents for their clinical information to be reported in the journal.